2011
DOI: 10.1002/eji.201041077
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of an antibody transgene requires AID and occurs by interchromosomal switching to all switch regions except the mu switch region

Abstract: Summary Immunoglobulin (Ig) class switch recombination (CSR) occurs most often by intrachromosomal recombinations between switch (S) regions located on a single chromosome, but can also occur by interchomosomal recombinations between Ig heavy chain (Igh) S regions located on chomosomal homologs. Interchromosomal recombinations have also been found between chromosomes that are not homologs; examples are Igh/c-myc and Igh/transgene translocations. Most, but not all, studies have indicated that activation-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Concomitantly to the finding that PARP inhibitors increase the sensitivity of DNA-PK-deficient cells to radiomimetic-induced DSBs [45], biochemical experiments [45,48,49] and plasmid assays in Kudeficient cells [61] substantiated the involvement of PARP1 in a non [62,71,82,95,100,116,118,[149][150][151][152]154,160,161,163,168,169,171,174,180,182,184,185,264,[305][306][307] Translocation IR, etoposide, Zn-finger nucleases [94,240,245,303,308] RAG, AID, spontaneous [62,95,100,152,154,162,163,171,240,261,269,…”
Section: End Recognition and Tethering Of Dsb Endsmentioning
confidence: 81%
See 1 more Smart Citation
“…Concomitantly to the finding that PARP inhibitors increase the sensitivity of DNA-PK-deficient cells to radiomimetic-induced DSBs [45], biochemical experiments [45,48,49] and plasmid assays in Kudeficient cells [61] substantiated the involvement of PARP1 in a non [62,71,82,95,100,116,118,[149][150][151][152]154,160,161,163,168,169,171,174,180,182,184,185,264,[305][306][307] Translocation IR, etoposide, Zn-finger nucleases [94,240,245,303,308] RAG, AID, spontaneous [62,95,100,152,154,162,163,171,240,261,269,…”
Section: End Recognition and Tethering Of Dsb Endsmentioning
confidence: 81%
“…This may also reflect a form of coupling between AID-mediated cleavage and the C-NHEJ machinery, although less stringent than between RAG-induced DSBs and C-NHEJ. This notion is further supported by the different ability of S compared to other S regions to participate in translocations [269]. Alternatively, the mechanism of production of DSBs, by affecting the nature of DNA ends, may influence the way they are processed by the A-EJ machinery, thus giving rise to more or less MH at the junction.…”
Section: End-joining Processes In Chromosomal Rearrangementsmentioning
confidence: 96%
“…Although to date we have not elucidated the mechanism, possible explanations include cis-recombination and interallelic class-switch recombination, which might point to a selection pressure of a particular immunological check point at the IgG Fc part during the rabbit B-cell cycle. [32][33][34][35][36][37][38][39] The analysis of the VDJ sequence in the transgenic rabbits revealed that approximately 82% of all sequences are correctly joined together, delivering a human huVH-D-huJH sequence. In matured IgG antibodies, the original rabbit-derived DH sequence is highly altered and quite antibody-specific so that it can hardly be assigned to a specific rabbit (or human) DH germline sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some recombination events take place in switch regions [32], others can take place even if donor transgenes lack switch regions [33]. Even though the majority of the recombination events require AID, a portion of the trans-recombination events may be independent of AID [36]. It seems likely that the final products of trans-recombination arise from multiple recombination pathways [32], [33], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the majority of the recombination events require AID, a portion of the trans-recombination events may be independent of AID [36]. It seems likely that the final products of trans-recombination arise from multiple recombination pathways [32], [33], [36].…”
Section: Discussionmentioning
confidence: 99%